The Ontological of State of Law of Pancasila as The Basis of Welfare State in Indonesia - Bagiastra, I Nyoman (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2020)
The rule of law as stated in the Constitution of the Republic of Indonesia, namely article 1 Section 3 of the 1945 Constitution which states explicitly that the State of the Republic of Indonesia is a rule of law, of course, has juridical consequences that must be accounted for in the practice of community life, nation, and state. By claiming to be a rule of law, Indonesia must fulfill and realize all the requirements and principles contained in a rule of law, namely the state has the obligation and provides legal certainty for protection to realize the welfare of its citizens. The research method used is normative legal research. the welfare state is briefly described as a series of public policies and state activities in integrating economic policies and social policies for the sake of achieving prosperity.